2013
DOI: 10.1111/jocn.12274
|View full text |Cite
|
Sign up to set email alerts
|

Developing a framework for nursing handover in the emergency department: an individualised and systematic approach

Abstract: Provision of a handover framework incorporating key features and essential information has the potential to improve the efficiency of handover. Use of this framework may enhance the transfer of accurate and essential information to enable safe and high standards of nursing care in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 34 publications
1
53
0
1
Order By: Relevance
“…A mixed methods study by Klim et al () found that nurses in emergency departments consider delivery of specified information to be the optimal method of handover, including noting the patients' details, reason for presentation, observations, and treatment plan. They detail that the information needs to be delivered in a systematic approach with reference to documentation such as charts and the involvement of the patient, patients' family, or carers (Klim et al, ). The PVITAL model, which initially started as the VITAL model, was specifically designed for emergency department use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixed methods study by Klim et al () found that nurses in emergency departments consider delivery of specified information to be the optimal method of handover, including noting the patients' details, reason for presentation, observations, and treatment plan. They detail that the information needs to be delivered in a systematic approach with reference to documentation such as charts and the involvement of the patient, patients' family, or carers (Klim et al, ). The PVITAL model, which initially started as the VITAL model, was specifically designed for emergency department use.…”
Section: Resultsmentioning
confidence: 99%
“…Several of these models include the DeMIST, ISOBAR, iSoBAR, ISBAR, SBAR, ICCCO, SHARED, VITAL, REED, and PVITAL mnemonics. The differing elements of these mnemonics have been extrapolated in Table (Bradley & Mott, ; Klim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of vital signs in handover as an integral part of ED shift change is also perceived by ED nurses to be important. The four top priorities for inclusion, over vital sign data, were patient details, presenting problem, the plan of care and treatment given (Klim et al, 2013). In an Australian study exploring ED nurse perceptions of current handover in the ED, nurses ranked vital signs as the 5th most important aspect of patient care that should be handed over at shift change in the ED (Klim, Kelly, Kerr, Wood, & McCann, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the Italian context communication systems in this regard may be underdeveloped, a fact which is mirrored in other countries internationally [20]. Structuring the handover process, through the use of mnemonic tools that prompt comprehensive reporting (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Structuring the handover process, through the use of mnemonic tools that prompt comprehensive reporting (e.g. the SBAR tool) is widely recommended for ED [20, 21]. However, recent reviews [21] reveal that even within this context there are uncertainties about reporting in some areas (e.g.…”
Section: Introductionmentioning
confidence: 99%